2013
DOI: 10.1590/s1984-82502013000200006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of total extracts of the leaves of Petiveria alliacea L. (Anamu)

Abstract: The antimicrobial activity of 13 total extracts was evaluated, 10 soft extracts (B) and 3 blended extracts (E) prepared from dry and fresh leaves of Petiveria alliacea L. Various solvents were used for their preparation: hydroalcoholic solution at 30%, 80% and isopropyl alcohol. The antimicrobial effect of the extracts was tested by means of the method of Kirby-Bauer, using four bacterial strains from the ATCC collection (Escherichia coli, Staphylococcus aureus, Enterococcus faecalis and Pseudomonas aeruginosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Previous studies evaluating its antimicrobial potential identified several antifungal and antibacterial labile organosulfur compounds from roots [16], such as thiosulfinates and sulfines with minimum inhibitory concentration (MIC) ranging between 16-128 μg/ml. The authors found these hydrophobic molecules are present in minor concentrations in this species, which may explain the relatively lower antimicrobial activity of P. alliacea in our work and also explain why some previous literature reports required higher extract concentrations to obtain relevant results [22].…”
mentioning
confidence: 43%
See 1 more Smart Citation
“…Previous studies evaluating its antimicrobial potential identified several antifungal and antibacterial labile organosulfur compounds from roots [16], such as thiosulfinates and sulfines with minimum inhibitory concentration (MIC) ranging between 16-128 μg/ml. The authors found these hydrophobic molecules are present in minor concentrations in this species, which may explain the relatively lower antimicrobial activity of P. alliacea in our work and also explain why some previous literature reports required higher extract concentrations to obtain relevant results [22].…”
mentioning
confidence: 43%
“…This has contributed to the natural selection of a large variety of plants capable of surviving under high-stress conditions, thanks to their International Journal of Pharmacology, Phytochemistry and Ethnomedicine Submitted: 2020-03-10 ISSN: 2297-6922, Vol. 16, pp [21][22][23][24][25][26][27][28][29][30][31][32] Accepted: 2020-09-11 doi:10.18052/www.scipress.com/IJPPE. 16.21 Online: 2021-02-04 CC BY 4.0.…”
Section: Introductionmentioning
confidence: 99%
“…The second study tracked also addresses the antinociceptive property of the species, but this time in murine models, confirming its analgesic potential in inflammatory contexts. Since then, the in vivo study, using animal models, has been the most applied, being present in 55.6% of the articles [ 2 , 6 , 9 , 21 , 22 , 23 , 24 , 25 , 26 , 28 , 30 , 34 , 36 , 37 , 41 , 42 , 44 , 45 , 48 , 50 , 53 , 54 , 55 , 56 , 57 , 58 ]. This is followed by in vitro tests, present in 27 works [ 2 , 6 , 9 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 28 , 30 , 34 , 36 , 37 , 41 , 42 , 44 , 45 , 48 , 50 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this decade, however, the highest number ( n = 494) and density of citations (d = 35,3 per paper) stood out. In the following decade, with the publication of 23 papers [ 10 , 11 , 13 , 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and a greater diversity of methodological approaches, including a literature review and ex vivo methods, we verified a significantly smaller impact, reaching just over half of the citations ( n = 278) of the previous period and having a citation density (d = 12 per paper) three times lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation